Hubungan Kualitas Tidur Dengan Status Hemodinamik Pada Pasien IMA Di Ruang ICVCU RSUD Dr. Moewardi Tahun 2016 - Syifa Mutia Desiani (Poltekkes Kemenkes Surakarta, 2018)
Background. Acute Myocardial Infraction can have unique manifestations in individual patients, such as shortness of breath, pale, headache, nausea, vomiting, and the most common presenting symptoms of myocardial infarction is chest pain. The clinical symptoms of a patient with Acute Myocardial Infarction (AMI) can cause a nursing problem and basic human problem. For example, chest pain can cause sleep problems. Sleep problems can influence the hemodynamics of a patient. The goal of this research is to find of correlation between sleep quality with a hemodynamic status of a patient with AMI. Methods. The research used descriptive analytic with the cross-sectional approach. The total sample is 30 respondents, assessing the quality of sleep using questioners sheet and to measure hemodynamic by observation sheet. Analysis of correlation data used a Spearman test. The Results. The result of research obtained 43,3% had mild sleep problems, 50% had moderate sleep problems, 6,7% had severe sleep problems. The result of analysis statistic with Spearman test shows that relationship between sleep quality with MAP obtained significance (p-value) 0,003, the relationship between sleep quality with heart rate obtained significance (p-value) 0,0001, and the relationship between sleep quality with respiratory rate obtained significance (p-value) 0,0001. Based on significance value there is a correlation between sleep quality with hemodynamic status (MAP, heart rate, respiratory rate) of patients with Acute Myocardial Infarction (AMI). Conclusion. There is a correlation between sleep quality with hemodynamic status (MAP, heart rate, and respiratory rate) of patients with Acute Myocardial Infarction (AMI) in ICVCU Dr.Moewardi Hospital.